Foreign investor ́s rights, investment promotion and facilitation agencies: a developmental and sustainable visión - Stanley, Leonardo (2020)
Fil: Stanley, Leonardo. CEDES. Centro de Estudio de Estado y Sociedad. Área de Economía; Argentina.